2012
DOI: 10.3109/17453674.2012.657579
|View full text |Cite
|
Sign up to set email alerts
|

Validity, reliability, and responsiveness of a self-reported foot and ankle score (SEFAS)

Abstract: Background and purpose A questionnaire was introduced by the New Zealand Arthroplasty Registry for use when evaluating the outcome of total ankle replacement surgery. We evaluated the reliability, validity, and responsiveness of the modified Swedish version of the questionnaire (SEFAS) in patients with osteoarthritis or inflammatory arthritis before and/or after their ankle was replaced or fused.Patients and methods The questionnaire was translated into Swedish and cross-culturally adapted according to a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 25 publications
3
75
0
4
Order By: Relevance
“…A relative drawback of the MOXFQ consists of the copyright licence, which is required for any use of the score, with administration fees for any version [52]. Limited validated translations of both instruments have been developed until now [48,53]. The psychometric properties of the quality of life scores, demonstrate the SF-36 meets quality criteria best.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relative drawback of the MOXFQ consists of the copyright licence, which is required for any use of the score, with administration fees for any version [52]. Limited validated translations of both instruments have been developed until now [48,53]. The psychometric properties of the quality of life scores, demonstrate the SF-36 meets quality criteria best.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of 12 items, with 3 subscales (pain, function and additional symptoms) [48]. Eight questions are derived from the Oxford-12-hip questionnaire; 4 questions are focussed on foot/ankle pathology [39].…”
Section: Disease-specific Outcome Measuresmentioning
confidence: 99%
“…Surgery becomes an option after failed non-surgical treatment. There are less than 20 published studies that evaluate the outcome of this type of surgery, most are small retrospective investigations [11][12][13][14][15][16][17][18][19] with only postoperative data presented [23][24][25][26] and only few use a prospective design [20][21][22]. The aim of this study was to prospectively evaluate surgery for stage II AAFD.…”
Section: Introductionmentioning
confidence: 99%
“…In our first study published 2012 we found that SEFAS has good psychometric properties in patients with inflammatory arthritis and osteoarthritis in the ankle [2]. This study was presented by M. Cö ster at the 9th International Congress of the European Foot and Ankle Society in Noodwijk, Netherlands in September 2012.…”
mentioning
confidence: 96%
“…We find it remarkable that the authors claim that such a PROM does not exist. Three papers concerning the Self-reported Foot and Ankle score (SEFAS) has been published by our group [2][3][4] and one based on the New Zealand Joint Registry [5]. At least two of these four papers were available when the paper by Witteveen was accepted in May 2014.…”
mentioning
confidence: 98%